The effect of vitamin D administration on vitamin D status and respiratory morbidity in late premature infants. Issue 11 (12th August 2020) - Golan‐Tripto, Inbal; Bistritzer, Jacob; Loewenthal, Neta; Staretz‐Chacham, Orna; Dizitzer, Yotam; Goldbart, Aviv
Abstract: Objective: To assess whether increment of vitamin D daily intake results in improved serum25(OH) vitamin D levels and reduced respiratory morbidity in premature infants. Methods: A randomized double‐blind clinical pilot trial, including preterm infants born at 32 + 6 to 36 + 6 weeks of gestation. The control group received 400 international units (IU) of cholecalciferol daily compared to 800 IU daily in the intervention group. Levels of 25(OH) vitamin D were measured at birth and 6 and 12 months of age. Respiratory morbidity was followed until 1 year of age. Results: Fifty subjects were recruited during the study period; the median measured 25(OH) vitamin D levels in the control vs intervention groups were: 26.5 vs 34 nmol/L ( P  = .271) at birth, 99 vs 75.5 nmol/L ( P  = .008) at 6 months and 72.5 vs 75 nmol/L ( P  = .95) at 12 months of age. Infants with insufficient vitamin D (<75 nmol/L) levels had higher respiratory morbidity. Serum vitamin 25(OH) D is a fair predictor for respiratory symptoms (area under the curve [AUC], 0.697; 95% confidence interval [CI], 0.509‐0.885; P  = .047) and for recorded acute respiratory illnesses (AUC, 0.745; 95% CI, 0.569‐0.922; P  = .012). Conclusion: Doubling the daily intake of vitamin D in premature infants did not increase serum 25(OH) vitamin D level, due to poor compliance in the intervention group. We found an inverse association between serum 25(OH) vitamin D and respiratory symptoms, indicating vitamin D deficiency is a fair predictor for respiratory morbidity.